A cross‐cultural study testing the universality of basic psychological needs theory across different academic subjects. Issue 4 (11th February 2018) - Erturan‐İlker, Gökçe and Quested, Eleanor and Appleton, Paul and Duda, Joan L.
Abstract: Basic Psychological Needs Theory (BPNT) suggests that autonomy‐supportive teachers can promote the satisfaction of students' three basic psychological needs (i.e., the need for autonomy, competence, and relatedness) and this is essential for optimal functioning and personal well‐being. The role of need satisfaction as a determinant of well‐being is understood to be invariant across contexts and cultures. The aim of this study is to test the invariance in the relationships between students' perceptions of their teachers' autonomy support and their psychological need satisfaction, enjoyment, concentration, and boredom across different school subjects (math, English, and physical education lessons) and across different cultures (England and Turkey). Questionnaires tapping the targeted variables in the three different lesson types were completed by students in schools in England and Turkey. Results from multilevel modeling analyses showed some support for the tenets of BPNT, albeit there were inconsistences among the strengths of the hypothesized relationships based on country and/or lesson type.